Islam and Terrorism in the Middle East (Czech Journal of International Relations, 2002)
Some of the most crucial aspects linking Islam and terrorism in the Middle East are the focus of this essay. First, the ambiguity of the Sharia, the Islamic code of religious law, towards terrorism is discussed, a source of wide-ranging interpretations. Different ways of how terrorism has made its way throughout the history of the Muslim world are explored. Two examples are used to prove that terrorism has actually never traditionally been central to the spread of Islam, nor has it served any other Islam-related purpose. An analysis of the Islamic extremist groups of the Assassins and Kharijites reveals that it has always been minority factions that have used the weapon of terrorism to force their views onto the majority population. It is argued that two streams of thought lie behind modern terrorism by Muslims in the Middle East: nationalism and Islamism. The author shows that the first ideology was potent until the late 1970s, then to be overshadowed by the powerful concept of Islamism in the last twenty-five years of the 20th century. The author dismisses the claim that these two streams of thought and the violence they incite are Islam-specific. Instead, she makes the case that they can be linked to the major global ideologies of the time, i.e. the fight for national liberation and attempts by the South to counter the hegemony of the North. The final part of the essay explores the ways in which Muslim countries in the Middle East tackle terrorism. The author lists key universal and regional legal documents, adding a detailed analysis of the regional treaties by the Arab League (1998) and the Organisation of Islamic Conference (1999). Typical attitudes in Middle Eastern Muslim countries-such as the distinction made between terrorism and the struggle for national liberation, the role of the Palestinian cause, an effort to eliminate deeper motives for terrorist behaviour or the concern for uprooting 'state-sponsored terrorism'-are highlighted.